2017
DOI: 10.2141/jpsa.0160047
|View full text |Cite
|
Sign up to set email alerts
|

Identification of <i>MC1R </i>SNPs and their Association with Plumage Colors in Asian Duck

Abstract: The melanocortin 1 receptor (MC1R) gene is a candidate functional gene that controls the pigment production in melanocytes. The aim of this study was to identify polymorphisms and investigate the effect of the MC1R gene on plumage coloration in duck breeds, including Korean native ducks. Initially, 34 individuals from seven duck breeds were sequenced, obtaining 12 polymorphisms. Five single nucleotide polymorphisms (SNPs) in the coding region were non-synonymous, with mutations corresponding to amino acid chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Previous research carried outonhaplotype analysis of the MC1R gene in Canidae found the highest numbers of missense polymorphisms in the dog and red fox (Nowacka et al, 2013). In addition, MC1R gene haplotypes of plumage color in Nageswari ducks were reconstructed and the haplotype AAGC showed the highest frequency (Sultana et al, 2017). The 35 haplotypes of MC1R gene found in the three HS chicken populations in the present study in agreement with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research carried outonhaplotype analysis of the MC1R gene in Canidae found the highest numbers of missense polymorphisms in the dog and red fox (Nowacka et al, 2013). In addition, MC1R gene haplotypes of plumage color in Nageswari ducks were reconstructed and the haplotype AAGC showed the highest frequency (Sultana et al, 2017). The 35 haplotypes of MC1R gene found in the three HS chicken populations in the present study in agreement with those studies.…”
Section: Discussionsupporting
confidence: 91%
“…However, mule ducks with GA genotype of c.52G>A and c.376G>A produced by crossing selected female Tsaiya ducks and Muscovy drakes displayed an extremely low plumage color grading result (grade 1-3). In the present study, we found that these base changes of SNP in the MC1R gene sequence led to changes in the amino acid (Sultana et al, 2017). It has been reported that no significant difference is found in MC1R mRNA expression between white and black feather bulb of ducks (Li et al, 2012), implying that these amino acid substitutions caused by non-synonymous SNP mutations might lead to structural conformational change of MC1R protein and have an effect on enhancing MC1R activity in plumage coloration.…”
Section: Discussionsupporting
confidence: 46%
“…Over the past decade, traditional selection of maternal lines of mule duck, including Tsaiya and Pekin ducks, have successfully improved mule ducks whose white plumage is generally accepted by consumers in Taiwan. Many studies have demonstrated the polymorphisms of genes involved in the melanogenesis pathway associated with plumage coloration between avian species (Hoque et al, 2013;Zhang et al, 2015;Ran et al, 2016;Sultana et al, 2017;Sultana et al, 2018). However, little is known about the relationship between gene polymorphism and plumage coloration in intergeneric hybrids.…”
Section: Yi-chen Tumentioning
confidence: 99%
“…The black-colored duck group contained the Korean native black and Nageswari ducks, whereas Korean native white and commercial Peking ducks were grouped as the white-colored duck population. Detailed information on the plumage color and pattern of the four Asian duck breeds examined in the current study were presented in our previous study of MC1R [ 16 ]. For the c.114T>G polymorphism of MITF , the T allele frequency (0.352) was considerably higher in the black-colored duck population than in the white-colored ducks (0.144).…”
Section: Resultsmentioning
confidence: 99%